Application of Testing-Tracing-Treatment Strategy in Response to the COVID-19 Outbreak in Seoul, Korea - Park, Yoojin (J Korean Med Sci, 2020)
BACKGROUND: Following the coronavirus disease 2019 (COVID-19) outbreak in Wuhan, China, a total of 637 patients had been diagnosed with the disease in Seoul as of May 2, 2020. Our study aimed to describe the impact of the 3T strategies (preemptive testing, prompt tracing and proper treatment) on the epidemiological characteristics of COVID-19 in Seoul. METHODS: The descriptive and explanatory analysis was carried out on critical indicators such as epidemiological characteristics and key duration of patient status change from January 24 to May 2 in Seoul before and after preemptive testing for patients under investigation associated with COVID-19 clusters. RESULTS: Preemptive testing increased the positive test rate (3.9% to 4.2%), an asymptomatic case at diagnosis (16.9% to 30.6%), and reduced the time from symptom onset to quarantine (4.0 to 3.0 days). Prompt tracing decreased unknown sources of infection (6.9% to 2.8%), the mean number of contacts (32.2 to 23.6), and the time-varying reproduction number R(t) (1.3 to 0.6). With proper treatment, only 2 cases of mortality occurred, resulting in a fatality rate of just 0.3%. CONCLUSION: In the first wave of the COVID-19 pandemic lasting 100 days, the effect of the 3T strategies flattened the curve and decreased the time during which infected individuals were contagious, thereby lowering the R(t) below 1 in Seoul.